Enhancing systemic lupus erythematosus care and outcomes through innovative interventions by the rheumatology initiative (tRi) in Ghana - Dey, Dzifa; Bobade, Rosetta; Katso, Bright; Issaka, Saudatu; Charis, Angela; Can Tamakloe, Abdul Aziz; Narh, Padiki (Frontiers in Lupus, 2024)
In this perspective, we highlight the progress made by tRi and underscore the importance of continued collaboration and support for rheumatology initiatives in resource-limited settings to improve its management and awareness. Compared to other countries, we experience the challenge of having a shortage of rheumatologists, but tRi, Ghana, has made significant paces in improving care through educational activities and targeted projects. The conclusions drawn from these interventions show advancements in awareness, capacity building, and research. We confirm that all authors participated in the conceptualization and design of the study, data collection, and/or in the writing and critical review of the manuscript. All collaborators have followed the instructions for the authors and have read and approved the manuscript.